Flexibility and real estate valuation under uncertainty : a practical guide for developers - Geltner, David, 1951-; De Neufville, Richard, 1939- (Wiley Blackwell, 2018)
Provides a revolutionary conceptual framework and practical tools to quantify uncertainty and recognize the value of flexibility in real estate developmentThis book takes a practical "engineering" approach to the valuation of options and flexibility in real estate. It presents simple simulation models built in universal spreadsheet software such as Microsoft Excel. These realistically reflect the varying and erratic sources of uncertainty and price dynamics that uniquely characterize real estate. The text covers new analytic procedures that are valuable for existing properties and enable a new, more profitable perspective on the planning, design, operation, and evaluation of large-scale, multi-phase development projects. The book thereby aims to significantly improve valuation and investment decision making. Flexibility and Real Estate Valuation under Uncertainty: A Practical Guide for Developers is presented at 3 levels. First, it introduces and explains the concepts underlying the approach at a basic level accessible to non-technical and non-specialized readers. Its introductory and concluding chapters present the important 'big picture' implications of the analysis for economics and valuation and for project design and investment decision making. At a second level, the book presents a framework, a roadmap for the prospective analyst. It describes the practical tools in detail, taking care to go through the elements of the approach step-by-step for clarity and easy reference. The third level includes more technical details and specific models. An Appendix discusses the technical details of real estate price dynamics. Associated web pages provide electronic spreadsheet templates for the models used as examples in the book. Some features of the book include:-'' 'Concepts and tools that are simple and accessible to a broad audience of practitioners;-'' 'An approach relevant for all development projects;-'' 'Complementarity with the author's Commercial Real Estate Analysis & Investments'the most-cited real estate investments textbook on the market. Flexibility and Real Estate Valuation under Uncertainty: A Practical Guide for Developers is for everyone studying or concerned with the implementation of large-scale or multi-phase real estate development projects, as well as property investment and valuation more generally.